(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Pediatric restorative materials are expected to restore form and function while reducing recurrent caries risk through antibacterial activity and fluoride release. Objective This in vitro study compared antibacterial efficacy against Streptococcus mutans and fluoride release of four contemporary pediatric restorative materials. Methods Disc specimens (n = 15/material) were fabricated from conventional glass ionomer cement (CGIC), resin-modified glass ionomer cement (RMGIC), giomer, and alkasite bioactive restorative material. Antibacterial efficacy was evaluated using agar diffusion zone of inhibition, direct-contact viable count reduction, and 48-hour biofilm biomass assay. Fluoride release was measured on days 1, 7, 14, and 28 using an ion-selective electrode. Data were analyzed using one-way ANOVA with Tukey post hoc testing and repeatedmeasures ANOVA (alpha = 0.05). Results: RMGIC produced the greatest inhibition zone (18.42 +/- 1.36 mm), followed by CGIC (16.81 +/- 1.22 mm), alkasite (14.76 +/- 1.09 mm), and giomer (12.93 +/- 1.18 mm) (p < 0.001). Direct-contact testing showed the highest bacterial reduction for RMGIC (73.8 +/- 5.6%) and CGIC (68.4 +/- 6.1%). Cumulative 28-day fluoride release was highest in CGIC (39.62 +/- 3.74 ppm) and RMGIC (35.47 +/- 3.18 ppm), with significantly lower release from alkasite (22.91 +/- 2.64 ppm) and giomer (18.35 +/- 2.21 ppm) (p < 0.001). Conclusion Glass-ionomer-based materials demonstrated superior fluoride release and antibacterial activity, while alkasite showed moderate performance. These findings support material selection according to caries risk, restoration site, and required handling properties. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S252-S258